ANALISIS PENGARUH LINGKUNGAN FISIK DAN LINGKUNGAN NON FISIK TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Studi pada Karyawan bagian Penunjang RSUD dr.Ashari Pemalang) - Prabaningtyas, Ken Etika; Djastuti, Indi (Diponegoro Journal of Management, 2019)
This study aims to analyze the influence of the physical environtment and non-physical environment on employee performane with moivation as the mediating variable.The population used in this study were 147 non-medical employees who are supporting departement of RSUD dr.Ashari Pemalang who had become permanent employees. The number of samples used in this study were 70 respondents taken by purposive method. The method of data collection is done through a questionnaire. This research uses path analysis using the SPSS 21 analysis tool.The result of this study show that the physical environment has a positive and significant effect on work motivation, a non-physical environment has a positive and significant on work motivation, the physical environment has a positive and significant effect on employee performance, and a non-physical environment has a positive and significant on employee performance. The results of this study also indicate that there is a mediating effect of work motivation variables between the influence of the physical environment and non-pysical environment on employee performance.